The Statistical Fragility of Single-Bundle vs Double-Bundle Autografts for ACL Reconstruction: A Systematic Review of Comparative Studies. Issue 12 (20th December 2021) - Ehlers, Cooper B.; Curley, Andrew J.; Fackler, Nathan P.; Minhas, Arjun; Rodriguez, Ariel N.; Pasko, Kory; Chang, Edward S.
Background: The statistical significance of a given study outcome can be liable to small changes in findings. P values are common, but imperfect statistical methods to convey significance, and inclusion of the fragility index (FI) and fragility quotient (FQ) may provide a clearer perception of statistical strength. Purpose/Hypothesis: The purpose was to examine the statistical stability of studies comparing primary single-bundle to double-bundle anterior cruciate ligament reconstruction (ACLR) utilizing autograft and independent tunnel drilling. It was hypothesized that the study findings would be vulnerable to a small number of outcome event reversals, often less than the number of patients lost to follow-up. Study Design: Systematic review; Level of evidence, 2. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the authors searched PubMed for comparative studies and randomized controlled trials (RCTs) published in select journals, based on impact factor, between 2005 and 2020. Risk-of-bias assessment and methodology scoring were conducted for the included studies. A total of 48 dichotomous outcome measures were examined for possible event reversals. The FI for each outcome was determined by the number of event reversals necessary to alter significance. The FQ was calculated by dividing the FI by the respective sample size. Results: Of the 1794 studies screened, 15 comparative studies were included for analysis; 13 studies were RCTs. Overall, the mean FI and FQ were 3.14 (IQR, 2-4) and 0.050 (IQR, 0.032-0.062), respectively. For 72.9% of outcomes, the FI was less than the number of patients lost to follow-up. Conclusion: Studies comparing single-bundle versus double-bundle ACLR may not be as statistically stable as previously thought. Comparative studies and RCTs are at substantial risk for statistical fragility, with few event reversals required to alter significance. The reversal of fewer than 4 outcome events in a treatment group can alter the statistical significance of a given result; this is commonly less than the number of patients lost to follow-up. Future comparative study analyses might consider including FI and FQ with P values in their statistical analysis.